The Role of the Teacher in Overcoming Students' Learning Difficulties During the Covid-19 Pandemic at Elementary School - Rahmadani, Elda; Dafit, Febrina (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study attempts to show how teachers helped Class IV students at 114 Pekanbaru State Elementary School overcome their academic challenges during the Covid-19 Pandemic. Qualitative descriptive research is the kind of study that this is. Three fourth-grade teachers and six fourth-graders served as the study's data sources. In this study, interview, observation, and documentation approaches were employed to collect data. The three stages of the Milles and Huberman approach for data analysis were data reduction, data presentation, and drawing conclusions. The findings demonstrated that students' learning challenges during the pandemic were mastering course material, students were less attentive in class, and students were easily bored in class. First and foremost, the teacher's job in helping students overcome their learning challenges is that of a motivator. Second, is the role of the instructor as a mentor. Third, is the managerial function of the teacher. Fourth, is the facilitatory function of the teacher. Fifth is the innovator's function as the instructor. Sixth, the educator's function as an assessor. According to the findings of this study, the fourth-grade teacher at Pekanbaru State Elementary School 114 plays a part in helping students who are struggling to learn during the Covid-19 Pandemic.